A Short Review for Ransomware: Pros and Cons - Shakir, Hasan Awni; Jaber, Aws Naser (Springer, Cham, 2018)
Recently, the software virus Ransomware spread like a cyclone wind. As a cyclone wind creates atmospheric instability, Ransomware similarly creates computer data instability. Each user moves in the direction of digitization. The user securely holds data in his/her computer, but what if the data are “abducted”. Ransomware is a software virus that parses user data. This software can lock the system in a manner in which a person is forced to pay a ransom to retrieve his/her data. Ransomware attacks not only home computers but also company computers. This software virus encrypts data such that it cannot be deciphered by a regular individual. Thus, an individual has to pay the ransom to decrypt the data. However, the generated files are unrecognized by the computer system. This study provides an intensive review of the WannaCry Ransomware, its effect on the world of information, and the preventive measures implemented to control this Ransomware.